The new linguistic pluralism in Apulia. The representation of the Georgian community in the local media - Nichil, Luigi Rocco (Romanica Olomucensia, 2022)
The Georgian community is certainly numerically smaller than other foreign communities in Apulia: however, it represents an interesting case study to understand some dynamics linked to recent migratory movements. The contribution examines the Georgian minority in terms of its specific historical and linguistic features, then analyses how it is described in the Apulian media. The Georgian minority in Apulia and the statistics related to the migratory dynamics from Georgia to Italy are based on the databases of the National Statistical Institute (ISTAT) and the Organization for Economic Co-operation and Development (OECD; it. OCSE), while the representation of Georgians in the media has been reconstructed through a non-systematic analysis of the digital archives of some Apulian media. The processing of statistical data has allowed us to describe the main characteristics of a minority - so far little-known - that in recent years has grown silently, but considerably, in northern Apulia. The examination of the local media, on the other hand, has highlighted some clichés related to this community, in particular the stereotype that all Georgians are connected to the mafia. In conclusion, the study proves how the characterization of the Georgian minority is often based on cultural prejudices that are difficult to eradicate. These stereotypes are conveyed - if not created - by the local and national media: in this way, the responsibility for the criminal episodes that involved some persons ends up falling on the whole of the Georgian community.
Keywords: Georgian language; linguistic minorities; Apulia; stereotypes; Georgian mafia